Effect of different starting techniques on sprint speed and lower extremity muscle activation for 50 m sprint - Huang, B. X.; Hsu, T. M.; Nai, H. F.; Lin, J. Z. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The block start position has long been regarded the best starting method for sprints. From the block start, the runner can more quickly enter the optimal running mode than from a standing start and achieve a faster start speed in the shortest time [1]. However, in recent years, the three-point start has been used in the 4*100 m relay, where those running second to fourth legs can choose to start in a standing or three-point starting position. Most of the studies have compared the differences in sprint performance between block and standing starts, but the three-point start has rarely been considered. Examining the process of sprinting is limited during field experiments, as effectively analyzing the muscle activation mode during each phase is challenging. Therefore, the purpose of this study was to explore the instant step point and lower extremity muscle activation of different starting techniques for 50 m sprinting.